Networks Are Associated With Depression in Patients With Parkinson’s Disease: A Resting-State Imaging Study - Liao, Haiyan; Cai, Sainan; Shen, Qin; Fan, Jie; Wang, Tianyu; Zi, Yuheng; Mao, Zhenni; Situ, Weijun; Liu, Jun; Zou, Ting; Yi, Jinyao; Zhu, Xiongzhao; et al. (Frontiers in Neuroscience, 2021)
Background: Disturbance of networks was recently proposed to be associated with the occurrence of depression in Parkinson’s disease (PD). However, the neurobiological mechanism of depression underlying Parkinson’s disease remains unclear. Objective: This study was conducted to investigate whether intra-network and inter-network brain connectivity are differently changed in PD patients with and without depression. Methods: 41 PD with depression (PDD) patients, 64 PD without depression (PDND) patients, and 55 healthy controls (HCs) underwent resting-state functional magnetic resonance imaging (fMRI). The default mode network (DMN), executive control network (ECN), salience network (SN), precuneus network (PCUN), and sensory-motor network (SMN) were extracted using independent component analysis (ICA), and then the functional connectivity (FC) values within and between these networks were measured. Results: PDD patients exhibited abnormal FC values within the DMN, ECN, SN, PCUN, and SMN. In addition, PDD patients demonstrated decreased connectivity between anterior SN (aSN) and bilateral ECN, between posterior SN (pSN) and dorsal DMN (dDMN), and between PCUN and dDMN/SMN/bilateral ECN. Connectivity within the left hippocampus of dDMN and the right medial superior frontal gyrus of aSN was significant predictors of depression level in PD patients. Conclusions: Aberrant intra- and inter-network FC is involved in several important hubs in the large-scale networks, which can be a biomarker for distinguishing PDD from PDND.